If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 1 = 1 + 8x Reorder the terms: 1 + 7x = 1 + 8x Add '-1' to each side of the equation. 1 + -1 + 7x = 1 + -1 + 8x Combine like terms: 1 + -1 = 0 0 + 7x = 1 + -1 + 8x 7x = 1 + -1 + 8x Combine like terms: 1 + -1 = 0 7x = 0 + 8x 7x = 8x Solving 7x = 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 7x + -8x = 8x + -8x Combine like terms: 7x + -8x = -1x -1x = 8x + -8x Combine like terms: 8x + -8x = 0 -1x = 0 Divide each side by '-1'. x = 0 Simplifying x = 0
| ab+5a-b-5=0 | | 18(v+3)-2v=4(4v+1)-11 | | 6/5:2,7 | | 4=p-36 | | -7+8p=-7-2p | | 8v-(8v-6)= | | -12-5y=-32 | | √25/289 | | 6x2/3x | | 5/6=1/2v | | -5-6(k+5)=-(k-5) | | 3a+7-8a= | | 6x+1=10x-1 | | 100+20(5.25)=x | | 3(w+1)=w+19 | | 6(x-1)=-3+6(x+8) | | (-4)-((-9/-9)-8) | | x^2=100-15x | | 159+12x=96-5x | | -29m=-1131 | | X-3X+4+8=X | | -40-6n=-3(8n-3) | | 7+3-4m=9 | | -7x-6y-4x+7y= | | -3x-(x-8)=-7-7x | | 144/16 | | 37+3v=2(4v+1) | | (6x+5)+(4x-2)=8x+21 | | 8x+77= | | 2m+15=31 | | (2x+4)+5=11 | | -35=x-37 |